2011
DOI: 10.1021/jp109958z
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Steam Treatment on Dye−Titania Complex Formation and Photoelectric Conversion Property of Dye-Doped Titania Gel

Abstract: Xanthene dye molecules form a chelate complex with the titanium species on the titania surface in dye−titania systems. The complex formation causes a fast electron injection into the titania conduction band. In this study, simple spectroscopic and photocurrent measurements of the xanthene dye-doped titania gels prepared by the sol−gel method were conducted in order to clarify the influence of a steam treatment on the dye−titania interaction and electron transfer. The photocurrent quantum efficiency of the fluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
111
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 35 publications
(118 citation statements)
references
References 37 publications
6
111
1
Order By: Relevance
“…The carboxyl group of benzoic acid was transformed into the carboxylate and formed a chelate complex with the titanium species as reported in the fluorescein-doped titania [14]. This is because the proton dissociation constant, pK a , of the carboxyl group of benzoic acid, i.e., 4.2, is close to that of fluorescein, i.e., 4.45 [32].…”
Section: Resultsmentioning
confidence: 73%
See 2 more Smart Citations
“…The carboxyl group of benzoic acid was transformed into the carboxylate and formed a chelate complex with the titanium species as reported in the fluorescein-doped titania [14]. This is because the proton dissociation constant, pK a , of the carboxyl group of benzoic acid, i.e., 4.2, is close to that of fluorescein, i.e., 4.45 [32].…”
Section: Resultsmentioning
confidence: 73%
“…It is important for the photofuel reaction that the benzoic acid molecules were highly dispersed and incorporated in the titania. As shown in Figure 5, the carboxylate bands of the doped benzoic acid indicate the strong interaction and a chelating linkage between the carboxylate and the titanium species [14].…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The shape of all the spectra was similar to the absorption spectra of titania exhibiting the absorption edge at around 400 nm. This indicated that the photocurrent was generated by the excited electrons in the titania [31,32]. Figure 4 shows the I-V curves of the electrode observed under the same conditions.…”
Section: Photocatalytic Reaction On the Electrodesmentioning
confidence: 82%
“…The compounds in such materials exhibit a more efficient light harvesting and fluorescence because they are finely dispersed in the amorphous or nanosized crystalline matrices compared to the conventional dye-adsorbing materials [20][21][22][23]. Therefore, it is expected that such films exhibit a higher function, stability, and performance in various applications.…”
Section: Introductionmentioning
confidence: 99%